2017
DOI: 10.1038/celldisc.2016.48
|View full text |Cite
|
Sign up to set email alerts
|

Arginine methylation of USP9X promotes its interaction with TDRD3 and its anti-apoptotic activities in breast cancer cells

Abstract: The Tudor domain-containing proteins are characterized by their specific interactions with methylated protein motifs, including methyl-arginines and methyl-lysines. The Tudor domain-containing protein 3 (TDRD3) is one of the major methyl-arginine effector molecules that recognizes methylated arginine residues on histones and the C-terminal domain of RNA polymerase II, and activates transcription. However, majority of the cellular TDRD3 localizes to the cytoplasm and its functions there are still elusive. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…Elevated ROS levels are associated with apoptosis and Bcl-2 is a critical regulator in ROS-associated apoptosis (4749), suggesting that apoptotic cell death caused at least a portion of the PDLSCs cell death under the treatment with H 2 O 2 . Multiple results have demonstrated the role of Bcl-2 in apoptosis and there is a need to identify the upstream regulators of Bcl-2 (5052). The present results demonstrated that the induction of Creb expression attenuated the H 2 O 2 -induced ROS elevation, suggesting that Creb protects PDLSCs from apoptosis by activating Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated ROS levels are associated with apoptosis and Bcl-2 is a critical regulator in ROS-associated apoptosis (4749), suggesting that apoptotic cell death caused at least a portion of the PDLSCs cell death under the treatment with H 2 O 2 . Multiple results have demonstrated the role of Bcl-2 in apoptosis and there is a need to identify the upstream regulators of Bcl-2 (5052). The present results demonstrated that the induction of Creb expression attenuated the H 2 O 2 -induced ROS elevation, suggesting that Creb protects PDLSCs from apoptosis by activating Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…The human PRMT1, PRMT3, CARM1/PRMT4, PRMT6 and PRMT8 cDNAs were cloned into a pGEX-6P-1 vector (GE Healthcare Life Sciences). The GST-Tudor (wild-type) and GST-Tudor (E691K) of TDRD3 have been described before ( 19 ). Human TOP3B cDNA and its truncated cDNAs (1-707 and 708–862) were cloned into pGEX-6P-1 and p3xFLAG-CMV vector (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…It is hence of high interest to uncover small molecule regulators of stress granules. In addition, a recent research disclosed that TDRD3 binds the methylated USPX9 and such interaction promotes the antiapoptotic activities of breast cancer cells . Hence, TDRD3 might serve as a new target for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…TDRD3 has also been identified as a regulator of proliferation and invasion of breast cancer cells . The Tudor‐mediated interaction between TDRD3 and ubiquitin‐specific protease 9 X‐linked suppresses the ubiquitination of TDRD3 and colocalizes this complex into stress granules, and such interaction promotes the antiapoptotic activities of breast cancer cells . These findings suggest TDRD3 as a new therapeutic target for breast cancers.…”
Section: Introductionmentioning
confidence: 95%